2007
DOI: 10.1128/aem.02101-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fusarium oxysporum β-1,6-Galactanase, an Enzyme That Hydrolyzes Larch Wood Arabinogalactan

Abstract: A type II arabinogalactan-degrading enzyme (FoGal1) was purified from Fusarium oxysporum 12S, and the corresponding cDNA was isolated. FoGal1 had high similarity to enzymes of glycoside hydrolase family 5. Treatment of larch wood arabinogalactan with the recombinant enzyme indicated that FoGal1 is a ␤-1,6-galactanase that preferentially debranches ␤-1,6-galactobiose from the substrate.Type II arabinogalactans in the Western larch consist of a ␤-1,3-galactan backbone with many side chains at position 6 (15). Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…Thus, programmed necrosis might occur when AeAl2 cells are infected with SFGR. Contrary to our results, a previous report found that some non-pathogenic SFGR species, R. montanensis , and R. peacockii , were able to grow in two mosquito cell lines (the A. albopictus cell line Aa23 and the Anopheles gambiae cell line Sua5B; Sakamoto and Azad, 2007). The reason for this discrepancy is poorly understood; however, the abovementioned growth was only detected by FISH and PCR, rather than in an infective assay.…”
Section: Tropism Of Rickettsiae Toward Arthropod Vectors and Culturedcontrasting
confidence: 99%
“…Thus, programmed necrosis might occur when AeAl2 cells are infected with SFGR. Contrary to our results, a previous report found that some non-pathogenic SFGR species, R. montanensis , and R. peacockii , were able to grow in two mosquito cell lines (the A. albopictus cell line Aa23 and the Anopheles gambiae cell line Sua5B; Sakamoto and Azad, 2007). The reason for this discrepancy is poorly understood; however, the abovementioned growth was only detected by FISH and PCR, rather than in an infective assay.…”
Section: Tropism Of Rickettsiae Toward Arthropod Vectors and Culturedcontrasting
confidence: 99%
“…When arabinan was isolated from black liquor and used as a substrate, arabinose was the major product. The enzyme substrate specificity is quite similar to that for the enzyme from F. oxysporum (FoGal1) (23). When FoGal1 hydrolyzed larch arabinogalactan, predominantly ␤-1,6-galactobiose and small amounts of galactose and arabinose were produced.…”
Section: Vol 74 2008 Endo-␤-16-galactanase From Streptomyces Avermmentioning
confidence: 55%
“…GH5_16 is another example of a monospecific subfamily of secreted enzymes where only a single fully sequenced biochemically characterized β-1,6-galactanase (EC 3.2.1.164) is currently known [32], although partial N-terminal sequence of an Aspergillus enzyme, closely related to sequences of other members of the subfamily, yields the same activity [33]. Several other enzymes with β-1,6-galactanase activity have been moved from GH5 to GH30_5 [23], but subfamily GH5_16 clearly remains within family GH5.…”
Section: Resultsmentioning
confidence: 99%
“…Several other enzymes with β-1,6-galactanase activity have been moved from GH5 to GH30_5 [23], but subfamily GH5_16 clearly remains within family GH5. The known β-1,6-galactanase (EC 3.2.1.164) is involved in larch wood arabinogalactan degradation [32]. …”
Section: Resultsmentioning
confidence: 99%